WEAI Resource Center Website - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Women are key to agricultural transformation in developing countries, but various obstacles and economic constraints limit their contributions to their households and communities. The Women’s Empowerment in Agriculture Index (WEAI) is an innovative tool that seeks to identify such obstacles, and may be used to track gender equality and measure empowerment, agency, and women’s inclusion in the agricultural sector.